Recent Approaches for Chemical Speciation and Analysis by Electrospray Ionization (ESI) Mass Spectrometry - Indelicato, Serena; Bongiorno, David; Ceraulo, Leopoldo (Frontiers in Chemistry, 2021)
In recent years, the chemical speciation of several species has been increasingly monitored and investigated, employing electrospray ionization mass spectrometry (ESI-MS). This soft ionization technique gently desolvates weak metal–ligand complexes, taking them in the high vacuum sectors of mass spectrometric instrumentation. It is, thus, possible to collect information on their structure, energetics, and fragmentation pathways. For this reason, this technique is frequently chosen in a synergistic approach to investigate competitive ligand exchange-adsorption otherwise analyzed by cathodic stripping voltammetry (CLE-ACSV). ESI-MS analyses require a careful experimental design as measurement may face instrumental artifacts such as ESI adduct formation, fragmentation, and sometimes reduction reactions. Furthermore, ESI source differences of ionization efficiencies among the detected species can be misleading. In this mini-review are collected and critically reported the most recent approaches adopted to mitigate or eliminate these limitations and to show the potential of this analytical technique.